Cortistatin regulates glucose-induced electrical activity and insulin secretion in mouse pancreatic beta-cells. (5th January 2019) - Soriano, Sergi; Castellano-Muñoz, Manuel; Rafacho, Alex; Alonso-Magdalena, Paloma; Marroquí, Laura; Ruiz-Pino, Antonia; Bru-Tarí, Eva; Merino, Beatriz; Irles, Esperanza; Bello-Pérez, Melisa; Iborra, Pau; Villar-Pazos, Sabrina; et al.
Abstract: Although there is growing evidence that cortistatin regulates several functions in different tissues, its role in the endocrine pancreas is not totally known. Here, we aim to study the effect of cortistatin on pancreatic beta-cells and glucose-stimulated insulin secretion (GSIS). Exposure of isolated mouse islets to cortistatin inhibited GSIS. This effect was prevented using a somatostatin receptor antagonist. Additionally, cortistatin hyperpolarized the membrane potential and reduced glucose-induced action potentials in isolated pancreatic beta-cells. Cortistatin did not modify ATP-dependent K + (KATP ) channel activity. In contrast, cortistatin increased the activity of a small conductance channel with characteristics of G protein-coupled inwardly rectifying K + (GIRK) channels. The cortistatin effects on membrane potential and GSIS were largely reduced in the presence of a GIRK channel antagonist and by down-regulation of GIRK2 with small interfering RNA. Thus, cortistatin acts as an inhibitory signal for glucose-induced electrical activity and insulin secretion in the mouse pancreatic beta-cell. Graphical abstract: Image 1 Highlights: Cortistatin inhibited glucose-stimulated insulin secretion from mouse islets. Cortistatin induced plasma membrane hyperpolarization in pancreatic beta-cells. This peptide did not affect the activity of KATP channels. Cortistatin activated channels with characteristics of GIRK channels. Down-regulation and antagonism of GIRK channels prevented the cortistatin effects.